1H NMR-based metabolomics study on the physiological variations during the rat pregnancy process. (5th March 2016) - Shen, Guiping; Li, Zhishui; Zhang, Yan; Wu, Huifeng; Feng, Jianghua
Abstract: In this study, NMR-based metabolomics in combination with multivariate pattern recognition technologies were employed to evaluate the physiological variations in the Wistar rats' plasma that are induced by pregnancy on the gestational days (GDs) 11, 14, 17 and 20. Untargeted metabolomics analysis revealed some possible mechanism of physiological effects for healthy pregnancies and showed a metabolic trajectory during pregnancy process. The levels of 24 metabolites were found to change significantly throughout pregnancy in maternal plasma. These metabolite changes involved in varied kinds of metabolic pathways including synthesis of biological substances, microbial metabolism in diverse environments, protein digestion and absorption, carbohydrate metabolism, digestion and absorption, mineral absorption, and ATP (Adenosine Triphosphate)-binding cassette transporters (ABC transporters). The substantial cores of all the metabolic pathways are promoting fetal growth and development and regulating maternal physiological state. This work showed relevant metabolic pathways perturbation in the maternal plasma due to normal pregnancy and provided the physical basis of time-dependent metabolic trajectory against which disease-related maternal physiological responses may be better understood in future studies. Highlights: NMR-based metabolomics were used to analyze the maternal physiological variations. Metabolic trajectory of maternal rats was visualized during pregnancy process. The metabolic changes reflect maternal physiological state and fetal development. These variations were involved in the varied kinds of metabolic pathways. The result may provide guidance on the implementation of eugenics in metabolism.